OZN in sodelovanje z zasebnim sektorjem - partnerstva na področju zagotavljanja humanitarne pomoči - Vidic, Manja (Teorija in praksa, 2016)
This article addresses public-private partnerships in the international context, a relatively unfamiliar topic in Slovenia. The contribution starts with key definitions pertinent to public-private partnerships with the United Nations and, through a historical overview, contextualizes them in broader cooperation with various stakeholders. It focuses on approaches and concrete partnerships in humanitarian aid and highlights common sets of obstacles encountered by actors on both ends. The concluding remarks provide an inkling of future trends on cooperation with the private sector and outline key principles on which sustainable partnerships should be built.
Keywords: Človekoljubna pomoč; Humanitarian assistance; International organizations; Javno-zasebno partnerstvo; Mednarodne organizacije; OZN; Private sector; Public-private sector cooperation; Zasebni sektor